Ultra-wide bandwidth electromagnetic wave and enhanced microwave absorption of Cu0.5Ni0.5Fe1.9Mn0.1O4 @CaTiO3 @MWCNTs nanocomposite in X-band frequency - Sani, Yusuf; Azis, Raba'ah Syahidah; Ismail, Ismayadi; Yaakob, Yazid; Abdul Karim, Muhammad Khalis; Mohammed, J.; Alhaji, Bello Murtala (Elsevier Ltd, 2023)
Broad bandwidth electromagnetic (EM) wave absorbers are persistently desired due to their massive applications in many fields. This paper reports the development of ultra-wide bandwidth microwaves, with the enhanced microwave absorption of thin-thickness absorbers. The design of RAMs requires a structure composed of magnetic-dielectric elements, meta-materials, and large impedance matching. This paper highlights the strategic approach to obtain the ultrawide, thin, and high impedance matching of the absorber. The Spinel-ferrite Cu0.5Ni0.5Fe1.9Mn0.1O4 (SF), Spinel ferrite doped calcium titanium oxide, Cu0.5Ni0.5Fe1.9Mn0.1O4@CTO (SF@CTO), and Spinel ferrite doped calcium‑copper titanate and multiwalled carbon nanotubes Cu0.5Ni0.5Fe1.9Mn0.1O4@CaTiO3@MWCNT (SF@CTO@MWCNT) nanocomposites absorbers were reported. The spinel ferrite and calcium copper titanite were synthesized via a co-precipitation method, and hydrothermally with the MWCNT by acid functionalization process. The effectiveness of microwave absorbing the samples was measured using a vector network analyzer with sample thicknesses of 1.0 mm, 2.0 mm, and 3.0 mm, in the frequency range of 8.0 to 12.0 GHz. The highest reflection loss (RL) of −33.3 dB at 9.6 GHz was anticipated using the complex permittivity and permeability characteristics. Interfacial electric polarisation, electromagnetic impedance matching, as well as the numerous scattering network structure of SF@CTO@MWCNT nanocomposites, are all credited with effective ultra-wide bandwidth microwave absorption. This report is important for paving future work in obtaining a desired thin and ultra-wide bandwidth absorber.